NEW GENERATION DRAWS THE LINE kosovo, east timor,and the "responsibility to protect" today. - Chomsky, Noam (ROUTLEDGE, 2025)
In this work, Chomsky explores the Wests uses and abuses of the principle of "human intervention." An updated foreword by Jean Bricmont explores the ongoing crises of humanitarian intervention in Afghanistan, Libya, Palestine, Syria, and Ukraine and reaffirms Chomskys excoriating critiques of Western foreign policy.Chomsky dissects the meaning and uses of humanitarian intervention grounded in the so-called "right to protect" (R2P). In doing so, Chomsky demonstrates how the principle of human intervention has been used as an instrument to justify military intervention in support of Western foreign policy aims. Through detailed case studies of the humanitarian intervention in East Timor and Kosovo, Chomsky also highlights how "humanitarian intervention" often leads to further atrocities and egregious abuses of human rights.As the question of humanitarian intervention looms ever larger, particularly with regard to the Middle East and Eastern Europe, this book is a vital overview of humanitarian intervention and its uses and abuses.